2020
DOI: 10.1038/s41598-020-76098-y
|View full text |Cite
|
Sign up to set email alerts
|

Using CHADS2 and CHA2DS2-VASc scores for mortality prediction in patients with chronic kidney disease

Abstract: Chronic kidney disease (CKD) is a public health issue and is associated with high morbidity and mortality. How to identify the high-risk CKD patients is very important to improve the long-term outcome. CHADS2 and CHA2DS2-VASc scores are clinically useful scores to evaluate the risk of stroke in patients with atrial fibrillation. However, there was no literature discussing about the usefulness of CHADS2 and CHA2DS2-VASc scores for cardiovascular (CV) and all-cause mortality prediction in CKD patients. This long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Thus, some misidentifications could exist. Comorbidity scores have been used for the prediction of stroke as well as other chronic diseases in recent studies [ 43 , 44 ]. For example, the CHA2DS2-VASc score includes risk factors such as age, sex, prior stroke history, diabetes, and hypertension [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some misidentifications could exist. Comorbidity scores have been used for the prediction of stroke as well as other chronic diseases in recent studies [ 43 , 44 ]. For example, the CHA2DS2-VASc score includes risk factors such as age, sex, prior stroke history, diabetes, and hypertension [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…CHA2DS2-VASc score was also used as a continuous variable to assess the risk, and was shown that CHA2DS2-VASc score is associated with a 38% increased risk for the composite endpoint [ 34 ]. Hsu et al evaluated the usefulness of CHADS2 and CHA2DS2-VASc scores for the prediction of CV and all-cause mortality in CKD [ 35 ]. Age, male gender, hypertension, heart failure and CHA2DS2-VASc score (HR 1.600; 95% CI 1.254–2.040; P < 0.001) were proven to be significant predictors of CV mortality.…”
Section: Cha2ds2vasc Score In Non-atrial Fibrillation Patients With Chronic Kidney Diseasementioning
confidence: 99%
“…Similarly, age, male gender, heart failure, CHA2DS2-VASc score (HR 1.503; 95% CI 1.300–1.739; P < 0.001) and angiotensin II receptor blockers use were significant predictors of all-cause mortality. Higher stage of CKD was also associated with increased all-cause mortality in CKD [ 35 ]. Recently, Vodošek Hojs et al performed a prospective study in non-dialysis CKD patients and assessed the role of CHA2DS2-VASc score in predicting CV and all-cause mortality in CKD.…”
Section: Cha2ds2vasc Score In Non-atrial Fibrillation Patients With Chronic Kidney Diseasementioning
confidence: 99%
“…The only similar study done in CKD patients was performed by Hsu et al [19]. They included 437 nondialysis CKD patients that were arranged for echocardiographic examinations because of suspecting coronary artery disease, hypertension, heart failure, abnormal cardiac physical examination, and survey for dyspnea.…”
Section: Disscussionmentioning
confidence: 99%
“…Our patients were stable at the time of inclusion, without having acute cardiovascular problems. Since the study by Hsu et al [19] was done in Taiwan, probably most of the patients were of Asian descent, while all our patients were Caucasian. Additionally, they did not perform laboratory examinations in the study and consequently could not add them to their analysis.…”
Section: Disscussionmentioning
confidence: 99%